Characterising the Intestinal Bacterial and Fungal Microbiome Associated With Different Cytokine Profiles in Two Bifidobacterium strains Pre-Treated Rats With D-Galactosamine-Induced Liver Injury - Zha, Hua; Li, Qian; Chang, Kevin; Xia, Jiafeng; Li, Shengjie; Tang, Ruiqi; Li, Lanjuan (Frontiers in Immunology, 2022)
Multiple probiotics have protective effects against different types of liver injury. Different intestinal microbes could be beneficial to the protective effects of the probiotics on the treated cohorts in different aspects. The current study was designed to determine the intestinal bacterial and fungal microbiome associated with different cytokine profiles in the Bifidobacterium pseudocatenulatum LI09 and B. catenulatum LI10 pre-treated rats with D-galactosamine-induced liver injury. In this study, Partition around medoids clustering analysis determined two distinct cytokine profiles (i.e., CP1 and CP2) comprising the same 11 cytokines but with different levels among the LI09, LI10, positive control (PC) and negative control (NC) cohorts. All rats in PC and NC cohorts were determined with CP1 and CP2 respectively, while the rats with CP1 in LI09 and LI10 cohorts had more severe liver injury than those with CP2, suggesting CP2 represented better immune status and was the “better cytokine profile” in this study. PERMANOVA analyses showed the compositions of both bacterial and fungal microbiome were different in the LI10 cohorts with different cytokine profiles, while the same compositions were similar between LI09 cohorts with different cytokine profiles. The phylotype abundances of both bacteria and fungi were different in the rats with different cytokine profiles in LI09 or LI10 cohorts according to SIMPER analyses results. At the composition level, multiple microbes were associated with different cytokine profiles in LI09 or LI10 cohorts, among which, Flavonifractor and Penicillium were the bacterium and fungus most associated with LI09 cohort with CP2, while Parabacteroides and Aspergillus were the bacterium and fungus most associated with LI10 cohort with CP2. These microbes were determined to influence the cytokine profiles of the corresponding cohorts. At the structure level, Corynebacterium and Cephalotrichiella were determined as the two most powerful gatekeepers in the microbiome networks of LI09 cohort CP2, while Pseudoflavonifractor was the most powerful gatekeeper in LI10 cohort with CP2. These identified intestinal microbes were likely to benefit the effect of probiotic Bifidobacterium on the immunity improvement of the treated cohorts, and they could be potential microbial biomarkers assisting with the evaluation of immune status of probiotics treated cohorts.